Cascading events in linked ecological and socioeconomic systems. Issue 4 (1st May 2007) - Peters, Debra PC; Sala, Osvaldo E.; Allen, Craig D.; Covich, Alan; Brunson, Mark
Abstract : Cascading events that start at small spatial scales and propagate non‐linearly through time to influence larger areas often have major impacts on ecosystem goods and services. Events such as wildfires and hurricanes are increasing in frequency and magnitude as systems become more connected through globalization processes. We need to improve our understanding of these events in order to predict their occurrence, minimize potential impacts, and allow for strategic recovery. Here, we synthesize information about cascading events in systems located throughout the Americas. We discuss a variety of examples of cascading events that share a common feature: they are often driven by linked ecological and human processes across scales. In this era of globalization, we recommend studies that explicitly examine connections across scales and examine the role of connectivity among non‐contiguous as well as contiguous areas. Los eventos consecutivos en cascada que empiezan a pequeñas escalas espaciales y que se propagan de forma no lineal a través del tiempo para influenciar áreas más grandes a menudo tienen impactos de gran envergadura sobre los recursos y servicios de los ecosistemas. La frecuencia y la magnitud de eventos tales como incendios y huracanes están aumentando mientras que los sistemas se interconectan por los procesos de la globalización. Necesitamos mejorar nuestra comprensión de estos acontecimientos para poder predecir su ocurrencia, reducir al minino los posibles impactos, y para permitir una recuperación estratégica. Aquí sintetizamos la información de estos eventos consecutivos en cascada en sistemas localizados a través del continente Americano. Discutimos una variedad de ejemplos de eventos consecutivos en casada que tienen una característica en común: son inducidos por procesos ecológicos y humanos ligados a través de las escalas. En esta era de globalización, recomendamos estudios que examinen explícitamente las conexiones a través de las escalas, y que se examine el rol de la conectividad entre áreas contiguas y no contiguas.